Quality of nursing recipes and mothers knowledge about supplementation with iron - Morales-Clemente, James (2020)
The present investigation had the objective of determining the relationship between the quality of nursing prescriptions and the mother's knowledge of iron supplementation. It was a quantitative, applied, descriptive, prospective, cross-sectional and correlational type of research. The sample was made up of 54 mothers who attended the Growth and Development Control Service of the ACLAS “Pillco Marca” of Huánuco, which were selected by the simple random type probabilistic sampling method. For data collection, a sociodemographic interview guide, a checklist to assess the quality of prescriptions, and the mother's knowledge questionnaire about iron supplementation to the child, previously validated and reliable, were used. The descriptive analysis was performed of the variables addressed and the hypothesis was verified using the Chi square test for p ≤ 0.05 and 95% confidence. The ethical considerations of the research were applied. The results show that when evaluating the quality of the nursing prescriptions, 83.3% (45) presented good quality and only 3.7% (2) were of poor quality, while the type of knowledge of the mothers on iron supplementation to the child / girl, it was correct in 79.6% (43) and only 20.4% (11) presented incorrectly. By contrasting the relationship between the variables, a value of X2 = 6,645 was obtained for a degree of freedom and p = 0.002, being significant. It is concluded that the quality of nursing prescriptions is related to the mother's knowledge of iron supplementation.